2017
DOI: 10.1089/cyber.2016.0503
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Contextual Cues in Virtual Environments and Creative Processes

Abstract: Because of the range of design possibilities they provide, virtual environments have a promising potential to support creative work. This article presents an experiment that explores the effects of contextual cues, provided in a virtual environment, on performance in a creative task. One hundred thirty-five participants completed a classical creativity task in one of three environments: a virtual creativity-conducive environment (CCE), comprising standardized elements identified from a survey as being characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 28 publications
0
45
0
3
Order By: Relevance
“…Creative performance is the ability to generate products, procedures or ideas that are considered to be original and potentially useful (Guegan, Nelson, & Lubart, 2017). In practical sense, creativity is related to the thinking of an employee and how their output contributes to the organization.…”
Section: Social Mediamentioning
confidence: 99%
“…Creative performance is the ability to generate products, procedures or ideas that are considered to be original and potentially useful (Guegan, Nelson, & Lubart, 2017). In practical sense, creativity is related to the thinking of an employee and how their output contributes to the organization.…”
Section: Social Mediamentioning
confidence: 99%
“…The results showed that the virtual environment influenced behavior and mutual perception of interlocutors congruently to the primed concepts. Finally, recent studies showed that virtual scenes tailored to the representation of a place conducive to creativity increased creative performance in comparison to a more neutral virtual environment (Guegan, Nelson, & Lubart, 2017a): when exposed to a bright, spacious and close to nature virtual environment, individuals produce more unique ideas and explore idea categories in greater depth than those exposed to a virtual meeting room. Another study showed that the content of the environment influenced the semantic categories of ideas produced (Nelson & Guegan, 2019): according to the type of virtual envi-ronment (underwater vs. forest), individuals produce more ideas that are semantically-related to the concepts primed by the environment.…”
Section: Introductionmentioning
confidence: 99%
“…A virtuális valóság alkalmazások oktatási felhasználása kiterjedt szakirodalommal rendelkezik (Ollé, 2012). A kreativitás és a virtuális valóság összefüggéseit is több kutatás vizsgálta az elmúlt években (Guegan és mtsai, 2016;Guegan, 2017;Ritter és mtsai, 2012;Yang és mtsai, 2018). Ezek arra engednek következtetni, hogy a virtuális térben a környezeti feltételek manipulálása révén fokozható a felhasználók kreatív teljesítménye.…”
Section: Virtuális Valóság éS Kreativitásunclassified
“…Az eredmények azt mutatták, hogy a feltaláló avatárokat használó csoport tagjai eredetibb és több ötletet hoztak létre, mint a többi csoport tagjai, sőt az azt követően elvégzett szemtől szembeni ötletgenerálás során is kreatívabb válaszokat adtak. Egy másik kísérletben Guegan (2017) azt vizsgálta, hogy a Second Life virtuális környezetben kialakított különböző jellemzőkkel rendelkező terek hogyan befolyásolhatják a felhasználók kreatív teljesítményét. A részt vevő 135 pszichológia szakos hallgató három kondícióban dolgozott egy kreatív probléma megoldásán: egy olyan virtuális térben, amelyet egy előzetesen elvégzett, a kreatív munkakörnyezet jellemzőire vonatkozó felmérés eredményei alapján alakítottak ki, egy valós tárgyalóban és a valós tárgyaló virtuális megfelelőjében.…”
Section: Virtuális Valóság éS Kreativitásunclassified